Development of survey instrument to evaluate student readiness in e-learning in Malaysia / Ng Set Foong, Chow Shiao Huey and Salwah Che Mat - Ng, Set Foong; Chow, Shiao Huey; Che Mat, Salwah (2009)
Survey is frequently done in order to obtain the opinion of a specific topic from a certain group of people. In this research, development of a survey instrument to evaluate student readiness in e-learning in Malaysia is focused. Then, the survey instrument is used in conducting a survey among university students in Malaysia taking technical courses. Development of a survey instrument involves specifying research objective, sampling design, construction of survey instrument, pretesting and pilot testing, validity and reliability assessment. Reliability analysis was conducted on the survey data. Moderate satisfactory level was observed on internal consistency reliability with Cronbach’s coefficient alpha between 0.458 and 0.788. From this study, it is found that the accessibility and availability of ICT infrastructure is satisfied. Furthermore, the percentage of students knowing how to use computer is also quite high. With these positive factors as background, the implementation of e¬learning in Malaysia is possible. However, the understanding and the acceptance level on e-learning among the respondents is not too satisfied. Therefore, the students should be exposed with more information and courses on how to use e-learning in their study. Furthermore, ICT literacy is shown to be the only factor that affects e-learning acceptance among the respondents in this study. Therefore, universities may introduce more ICT elements in course content, providing incentives for e-learning users and providing short-courses on ICT in order to increase ICT literacy among university students.